2007
DOI: 10.1007/s00125-006-0589-5
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine kinase 1 participates in insulin signalling and regulates glucose metabolism and homeostasis in KK/Ay diabetic mice

Abstract: Aims/hypothesis The aim of this study was to determine the potential role of sphingosine kinase 1 (SPHK1), a key sphingolipid metabolic enzyme, in glucose metabolism and homeostasis. Methods SMMC-7721 hepatoma cells and C2C12 myotube cells were used to explore the role of SPHK1 in glucose uptake in vitro. KK/Ay type 2 diabetic mice, which were transfected with adenovirus harbouring the human SPHK1 gene by i.v. injection, were used to investigate the glucoselowering effects of SPHK1 in vivo.Results The basal gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 45 publications
4
62
1
Order By: Relevance
“…Thus, an insulin-mimetic effect of S1P occurs in skeletal muscle as the pharmacological inhibition of Sphk1 diminishes insulin-mediated glucose uptake, while its overexpression mimics insulin action in vivo [34]. Moreover, S1P shares with insulin the ability to elicit the differentiation of myoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an insulin-mimetic effect of S1P occurs in skeletal muscle as the pharmacological inhibition of Sphk1 diminishes insulin-mediated glucose uptake, while its overexpression mimics insulin action in vivo [34]. Moreover, S1P shares with insulin the ability to elicit the differentiation of myoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…In rat adipocytes, S1P increases lipolysis and suppresses insulin-induced leptin secretion, consistent with a role in promoting insulin resistance (18). However, Ma et al (24) showed that adenoviral-mediated expression of human SK1 in KK/Ay T2D diabetic mice (Ad-SPHK1) reduced blood glucose levels and improved insulin sensitivity. In this instance, the effect of SK1 gene delivery on the tissue distribution of ceramide in these mice was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that such a rheostat may also exist for metabolic regulation. In stark contrast to ceramide, S1P promotes nutrient uptake (63) and increases basal and insulin-stimulated glucose uptake (64,65). The molecule has been shown to activate Akt/PKB in a wide variety of cell types (45,66,67).…”
Section: Figurementioning
confidence: 99%